Early exercise boundaries for American-style knock-out options - Nunes, J.; Ruas, J.; Dias, J. C. (European Journal of Operational Research, 2020)
This paper proposes a novel representation for the early exercise boundary of American-style double knock-out options in terms of the simpler optimal stopping boundary of a nested single barrier contract. Such representation only requires the existence, continuity and monotonicity (in time) of the nested single barrier exercise boundary, and these requirements are proved for the whole class of single-factor exponential-Lévy processes. To illustrate the practical relevance of our results, a new put-call duality relation is obtained, a real options application is provided and the Fourier space time-stepping method, the COS approximation, and the static hedging portfolio approach are all adapted to the valuation of American-style double knock-out options.